Jejak Tinggalan Peralatan Obsidian Temuan Terbaru di Kawasan Danau Bandung Purba - Nurul Laili (PANALUNGTIK, 2022)
The City of Bandung and its surrounding, was once a lake known as Bandung Purba Lake in the past. The current form is known as the "Bandung Basin". The area around the basin was assumed as the shores of the lake hence many remnants of past human activities were discovered. The dominant kind of discoveries found on the shores of the Bandung Purba Lake were obsidian tools, furthermore, other artifacts such as pickaxes and pottery also discovered. This article focuses on the obsidian tools. The existence of artifacts around Lake Bandung was adjusted to the life necessities and the availability of the materials. For this reason, this article will reveal the form of the remains made of obsidian on the site of the Bandung Purba Lake area. The method that being used is a descriptive method with an artifact-oriented analysis approach. The analysis showed that there were several forms of the remains such as flakes (used and retouched), core stones, sharp edges, knives/blades, and waste in the form of chips. Obsidian artifacts in the Bandung Purba Lake area can be grouped into two, the tool group and the non-tool group.